THE EFFECT OF AUDIT COMMITTEE EFFECTIVENESS, PROFESSIONAL COMITMENT, TENURE OF PUBLIC ACCOUNTANT FIRM, AND COMPETITION BETWEEN PUBLIC ACCOUNTING FIRMS AND AUDIT FEE ON THE INDEPENDENCE OF PUBLIC ACCOUNTING FIRMS - Yoga Saputra; Rahmi Aulia; Rieka Ramadhaniyah; Adinda Choirul Ummah (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The purpose of this study was to obtain empirical evidence about the effect of the audit committee effectiveness, professional commitment, tenure of public accounting firms, and competition between public accounting firms and audit fees on the independence of public accounting firms. The case study was on Public Accounting Firm in Southern Sumatra. This study used primary data with a distributed questionnaire to public accounting firms in Southern Sumatra. The questionnaire was also completed with simple and clear filling instructions to help respondents complete the questionnaire. The result of this study found that the effectiveness of the audit committee, professional commitment, tenure of public accounting firms, and audit fees had a significant effect on the independence of the public accounting firm in Southern Sumatra. Meanwhile, the competition among public accounting firms did not have a significant effect on the independence of public accounting firms.Keyword: Audit Committee Effectiveness, Professional Commitment, Tenure of Public Accounting Firms, Competition Between Public Accounting Firms, Audit Fees, Independence of Public Accounting Firms